Chemical recycling of waste polystyrene by thermo-catalytic pyrolysis: A description for different feedstocks, catalysts and operation modes. (July 2022) - Inayat, Amer; Fasolini, Andrea; Basile, Francesco; Fridrichova, Dagmar; Lestinsky, Pavel
Highlights: Thermo-catalytic pyrolysis of different PS-based waste plastics was carried out. Influence of different catalysts and operation modes was studied. Oil with high styrene content was obtained as major product for all feedstocks. Solid base catalysts influence the products only slightly compared to thermolysis. Solid acid catalyst promotes the formation of benzene, toluene and ethylbenzene. Abstract: Chemical recycling by thermo-catalytic pyrolysis/degradation offers the possibility of converting waste plastics into their original monomers or other valuable chemicals which can be used as feedstocks in chemical and petrochemical industries. Plastic wastes of polystyrene (PS) based materials can be a good source of styrene as well as mono-aromatic (BTEX: benzene, toluene, ethylbenzene, xylenes) compounds. The selectivity of pyrolysis products can be tuned by choosing the right catalyst as well as appropriate operating conditions/operation modes. In this regard, the focus of the present work was to perform thermo-catalytic pyrolysis of different waste polystyrene (WPS) feedstocks over acid and base catalysts employed in ex-situ and in-situ modes. The main goal was to compare the compositions of pyrolysis products obtained by changing feedstocks, catalysts and operation modes. A further goal was to discuss the suitability of the catalysts employed for the enhanced recovery of desired products from WPS pyrolysis. It was demonstrated that expanded polystyrene gives very similar product distribution as compared to virgin PS, both giving high styrene content. Likewise, hard PS-based random packing materials produce similar results as compared to high impact polystyrene (HIPS). Moreover, it was shown that solid base catalysts influence the composition of the pyrolysis products only slightly as compared to thermolysis. Solid acid catalyst however, showed significant impact on the composition of the pyrolysis products as compared to non-catalytic pyrolysis. These results may provide new insights for the chemical recycling of plastic wastes.